Hydrothermal synthesis of novel heterostructured Ag/TiO2/CuFe2O4 nanocomposite: Characterization, enhanced photocatalytic degradation of methylene blue dye, and efficient antibacterial studies. (6th June 2022) - Adarsha, J. R.; Ravishankar, T. N.; Ananda, A.; Manjunatha, C. R.; Shilpa, B. M.; Ramakrishnappa, T.
Abstract: In this work, we reported the successful synthesis of novel Ag/TiO2 /CuFe2 O4 ternary nanocomposite by hydrothermal technique by using TiO2 /CuFe2 O4 binary nanocomposite precursor that was also prepared by hydrothermal treatment by using TiO2 nanoparticles and CuFe2 O4 nanoparticles synthesized via sol–gel method. The synthesized nanomaterials were accessed for their morphological, structural, and optical properties. X‐ray diffraction (XRD) study reveals the formation of pure Ag/TiO2 /CuFe2 O4 ternary nanocomposite in which the Ag, TiO2, and CuFe2 O4 are in anatase, spinal, and cubic crystal phases, respectively. Transmission electron microscopy (TEM) and high‐resolution TEM (HRTEM) analyses of Ag/TiO2 /CuFe2 O4 ternary nanocomposite indicated granule‐shaped morphology with bright spots of silver. The existence of Ti, O, Cu, Fe, and Ag without any other elements in the energy‐dispersive X‐ray spectroscopy (EDS) spectra of the prepared ternary nanocomposite depict its purity and its polycrystalline nature was confirmed by its selected area electron diffraction (SAED) pattern. The ternary nanocomposite was utilized for the methylene blue dye degradation with an optimum dose of 1.00 g/100 ml under ultraviolet (UV) light; the enhanced photocatalytic activity of the composite is attributed mainly due to the appreciable magnitudinal difference of positive charge of the valence band and negative charge of the conduction band of TiO2 and CuFe2 O4 ; meanwhile, the interfacially placed Ag acts as a sink for the elections. Also, the ternary nanocomposite showed satisfactory antibacterial activities. Practitioner Points: The prepared ternary nanocomposite showed effective results in dye degradation and satisfactory antibacterial property. The concentration of methylene dye has decreased considerably in every degradation process which was accessed through UV‐vis studies. The highest degradation by using the ternary nanocomposite archived at pH = 6 Appreciable antibacterial activity was achieved against a few Gram‐positive strains and Gram‐negative strains of bacteria. This research activity can open a broad area of research towards textile dye degradation and antibacterial studies. Abstract : In this work, we report the successful synthesis of novel Ag/TiO2 /CuFe2 O4 ternary nanocomposite by hydrothermal technique by using TiO2 /CuFe2 O4 binary nanocomposite precursor that was also prepared by hydrothermal treatment by using TiO2 nanoparticles and CuFe2 O4 nanoparticles synthesized via sol–gel methods and utilized for photocatalytic and antibacterial activities.